Analisi costo/efficacia di sevelamer nel trattamento dell’iperfosforemia del paziente in dialisi - Eandi, Mario; Giotta, Nicola; Barbone, Gaia Santagostino (Farmeconomia. Health Economics and Therapeutic Pathways, 2004)
Dialysis-associated hyperphosphatemia has been treated with chelating calcium salts, in particular with calcium carbonate. A new option for the management of this problem is represented by sevelamer, a chelating agent which contains no calcium and no metals. Sevelamer and calcium carbonate are more or less equally effective and tolerated. The prolonged use of sevelamer instead of calcium carbonate, nevertheless, reduces calcemia and C-reactive protein levels, with a consequent reduction in myocardial infarction, angina pectoris and other peripheral vasculopathies. The limit to the wide-spread use of sevelamer is in its very high acquisition cost, as compared to the alternative. In this article, a semi-markovian pharmacoeconomical model for the comparison of clinical and economical outcomes of sevelamer and calcium carbonate is presented. The analysis is conducted in the perspective of the Italian health system (SSN). Clinical data are derived from published studies and integrated with expert panel estimates, cost data are relative to the Italian setting. The incremental cost-effectiveness analysis indicated that sevelamer is more costly, but also more costeffective: a one month gain in survival costs the SSN additional 2710 Euro, a value inferior to the conventionally accepted willingness-to-pay of industrialised countries. The majority of this excess cost is derived from the gain in survival, and consequent increase in dialysis costs. Thus, the choice of using sevelamer instead of calcium carbonate is even more justified from an ethical point of view. Sensibility analyses confirmed the robustness of the basic scenario results.